Efficacy of different treatment modalities for acute and chronic phases of the febrile infection-related epilepsy syndrome: A systematic review. (July 2020) - Kessi, Miriam; Liu, Fangyun; Zhan, Yalan; Tang, Yulin; Wu, Liwen; Yang, Lifen; Zhang, Ci-Liu; Yin, Fei; Peng, Jing
Highlights: 12.2% of the cases with febrile infection-related epilepsy syndrome (FIRES) die. 11.4% have autoantibodies, and the most common are anti-glutamate. The ketogenic diet is a potential treatment modality in the acute phase. Deaths occur because of the progress of the disease rather than complications of the drugs. Abstract: Background: Febrile infection-related epilepsy syndrome is associated with high mortality and morbidity rates. No systematic review of demographics, aetiologies, good treatment options, and causes of deaths has been performed. Thus, we aimed to focus on these factors to provide a structure for patient management and research. Methods: A deep literature search was performed in PubMed and Embase of all years until May 2019. Results: We retrieved 45 aSrticles: 3 multicentre cohort studies, 13 single-centre cohorts, 1 case series, and 28 case reports. We identified 229 cases: most were from Asia; 53% were males; 11.4% had several types of antibodies, and the most common was anti-glutamate receptor epsilon 2; 30% (69 cases) had good treatment outcomes; 12.2% died; and 56% remained with drug-resistant epilepsies. Univariate analysis revealed a statistically significant association between positive outcomes in Japan and China, the use of the ketogenic diet either acutely or chronically, and the use of steroids acutely or chronically. Taiwan showed a statistically significant association with negative outcomes. Multivariate logistic regression revealed the utilisation of the ketogenic diet in the acute phases (P = 0.008, OR = 3.613) and being in Japan (P = 0.003, OR = 3.146) as independent determinants of positive outcomes. Most of the deaths occurred because of the progress of the disease rather than complications of the drugs. Conclusions: Asians are more affected and several cases have antibodies. Positive outcomes are associated with being in Japan and the utilisation of the ketogenic diet in the acute phase.